Kinetic imaging of chlorophyll fluorescence using modulated light - Nedbal, L; Soukupová, J; Kaftan, D; Whitmarsh, J; Trtílek, M (Photosynthesis research, 2000)
Fluorometers that measure the kinetics of chlorophyll fluorescence have become invaluable tools for determining the photosynthetic performance of plants. Many of these instruments use high frequency modulated light to measure the rate, efficiency and regulation of photosynthesis. The technique is non-invasive and is effective under diverse environmental conditions. Recently, imaging fluorometers have been introduced that reveal variability in photosynthesis over the surface of a leaf or between individual plants. Most imaging instruments depend on continuous light or low frequency modulated light for fluorescence excitation, which imposes serious limitations on measurements of the fluorescence parameters, especially the minimum fluorescence (F(0)) and variable fluorescence (F(V)). Here, we describe a new instrument that combines the advantage of high frequency modulated light with two-dimensional imaging of chlorophyll fluorescence. The fluorometer produces dynamic images of chlorophyll fluorescence from leaves or plants, providing accurate mapping of F(0) and F(V), and non-photochemical quenching. A significant feature of the instrument is that it can record fluorescence images of leaves in daylight under field conditions.